True proximal third arm replantation: A rare case (Indian Journal of Case Reports, 2018)
Proximal arm replants are devastating injuries which leave significant disability for the patient. Replantation of proximal limb injuries is widely considered to have poor results, especially so of the proximal third of the arm due to the difficulty in anastomosis of the vessels in the axilla. Furthermore, crush avulsion injuries have a much worse prognosis than clean-cut injuries. Here, we present the successful replantation of a true proximal crush amputation of the upper limb at the level of proximal third arm with satisfactory results in a 19-year-old male.